Logistic Regression Analysis of Factors Influencing Mobile Application Adoption in Smallholder Livestock Farming: A Case Study from Northern Thailand - Saengwong, S.; Kongmuang, N.; Intawicha, P.; Sakphoowadon, S. (Faculty of Animal Science, IPB University, 2025)
This study examines the factors affecting the adoption of mobile farming management applications by smallholder livestock farmers in Northern Thailand. Data from 300 farmers were analyzed using binary logistic regression to evaluate 14 independent variables and their influence on application use. Four significant factors were identified: education level, participation in training programs, extension support, and membership in farmer associations. Education and participation in training programs were highly significant (p<0.001), whereas extension support and membership in farmer associations were both significantly associated with mobile application use (p<0.01 and p<0.05). Our findings indicate that educational initiatives, training programs, and strong extension support are crucial in enhancing mobile application adoption. Farmer associations also play a vital role in promoting technology use through peer influence and social networks. These insights highlight the importance of targeted strategies to improve mobile application adoption, thereby contributing to more efficient livestock management practices. To create practical and long-term digital solutions specifically designed to meet smallholder farmers’ requirements, it is essential to gain an in-depth understanding of these elements. The findings highlight the importance of addressing educational gaps, promoting training programs, and enhancing extension services to encourage technology adoption among smallholder farmers. By focusing on these critical factors, farmers can increase their adoption of mobile applications, thereby improving livestock management efficiency and enhancing the adaptability of smallholder farming systems in rural areas.